EVALUATION OF ANTIBIOTIC USE USING THE ATC/DD AND DU 90% METHODS IN OUTPATIENT PATIENTS IN PUSKESMAS RI TENAYAN RAYA - Novia Sinata; Delvi Regika; Mira Febrina (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Infectious diseases are one of the health problem that threaten developing countries, including Indonesia. Riau as one of the provinces with its coastal coverage is not spared from this problem. Inaccurate use of antibiotics is found in the wider community, which can be a cause of negative risks such as antibiotic resistance. Antibiotics are drugs that are used to treat diseases caused by microbes. The improper use of antibiotics can lead to a risk of resistance. Resistance can be avoided using antibiotics. This study aimed to classify antibiotic use using ATC codes and determine the quantity of antibiotic use in outpatients by calculating the DDD. This research method was observational, with a descriptive design and retrospective data collection using secondary data by searching medical records. The sample in this study consisted of outpatients at the Tenayan Raya Inpatient Health Center Outpatient Installation between January and December 2022 who received antibiotic therapy with an ATC code and DDD value in accordance with the provisions of the WHO Collaborating Center, using a total sampling technique.The results of the study showed that based on the ATC/DDD and DU 90% methods, there were 3 antibiotics with the highest quantity of use, namely amoxicillin at 165,92 DDD/1000 KPRJ with a percentage of 67,02%, ciprofloxacin at 41,07 DDD/1000 KPRJ with a percentage of 16,59 %, and cefixime as much as 14,69 DDD/1000 KPRJ with a percentage of 5,93%.  Keywords: antibiotics, ATC/DD, DU 90%, resistance